Obesity and Gastrointestinal Diseases. (27th May 2013) - Fujimoto, Ai; Hoteya, Shu; Iizuka, Toshiro; Ogawa, Osamu; Mitani, Toshifumi; Kuroki, Yuichiro; Matsui, Akira; Nakamura, Masanori; Kikuchi, Daisuke; Yamashita, Satoshi; Furuhata, Tsukasa; Yamada, Akihiro; et al.
Abstract : The prevalence of obesity in the Japanese population has been increasing dramatically in step with the Westernization of lifestyles and food ways. Our study demonstrated significant associations between obesity and a number of gastrointestinal disorders in a large sample population in Japan. We demonstrated that reflux esophagitis and hiatal hernia were strongly related to obesity (BMI > 25) in the Japanese. In particular, obesity with young male was a high risk for these diseases. On the other hand, it has been reported that obesity is also associated with Barrett's esophagus and colorectal adenoma; however, obesity was not a risk factor for these diseases in our study. The difference of ethnicity of our subjects may partly explain why we found no data to implicate obesity as a risk factor for Barrett's esophagus. Arterial sclerosis associated with advanced age and hyperglycemia was accompanied by an increased risk of colorectal adenoma.